Genome engineering of Clostridium difficile using the CRISPR-Cas9 system. (October 2018) - Wang, S.; Hong, W.; Dong, S.; Zhang, Z.-T.; Zhang, J.; Wang, L.; Wang, Y.
Abstract: Objectives: Clostridium difficile is a notorious pathogenic species that can cause severe gastrointestinal infections in humans and animals. C. difficile infection (CDI) results in thousands of deaths worldwide every year. The elucidation of related mechanisms of CDI and exploration of potential therapeutic strategies are largely delayed due to the lack of efficient genetic engineering tools for C. difficile strains. Methods: Plasmids carrying the CRISPR-Cas9 system were constructed and transformed into C. difficile through conjugation. Mutants were identified using colony PCR with primers annealing to the regions flanking the target gene deletion/integration locus. Heat-survival assay was used to compare the sporulation frequency between the mutant with spo0A deletion and the wild type strain. The fluorescence in the mutant with the insertion of the green fluorescent protein (GFP) gene was inspected under a fluorescent microscope. Results: An efficient genome editing tool was developed for C. difficile based on the CRISPR-Cas9 system. With this tool, spo0A was deleted with a 100% mutation efficiency. Conversely, an anaerobic GFP gene was successfully inserted into the C. difficile chromosome (with a mutation efficiency of 80%). Conclusions: The developed CRISPR-Cas9-based genome engineering tool will facilitate functional genomic studies in C. difficile as well as the elucidation of mechanisms related to host–bacteria interaction and pathogenesis of CDI. This will be highly beneficial for the development of innovative strategies for CDI diagnostics and therapies.